Systematic Review of the Strategies to Address Health Worker Shortage in Rural and Remote Areas of Low- and Middle-Income Countries - Gillian I. Adynski; Leah L Morgan (Online Journal of Rural Nursing and Health Care, 2021)
Purpose: The aim of this paper is to examine the literature on strategies to address the maldistribution of health workers between urban and rural and remote areas of low- and middle-income countries.